2007
DOI: 10.1088/0022-3727/40/8/022
|View full text |Cite
|
Sign up to set email alerts
|

The coupling vibration of fluid-filled carbon nanotubes

Abstract: Carbon nanotubes (CNTs) have substantial promise as nanocontainers filled with fluid in their hollow cavity in nanotechnology. This paper reports the result of an investigation into the influence of internal fluid on the coupling vibration of fluid-filled CNTs. The coupling vibrational behaviour of fluid-filled CNTs under different supported ends, aspect ratio, surrounding elastic medium, mass density of the fluid and layer number is investigated. The results obtained describe the effect of end condition, aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, getting the theoretical boundary conditions to simulate the actual stiffness of the supports is still a challenge, in particular for nanostructures [30]. Consequently, to show the effects of the boundary stiffness on the vibration characteristics of CNTs, typical and standard boundary conditions are usually applied [21][22][23][24][25][26]. As mentioned above, this model has been solved for P-P, C-P and C-C conditions.…”
Section: The Effects Of the Boundary Conditionsmentioning
confidence: 99%
“…However, getting the theoretical boundary conditions to simulate the actual stiffness of the supports is still a challenge, in particular for nanostructures [30]. Consequently, to show the effects of the boundary stiffness on the vibration characteristics of CNTs, typical and standard boundary conditions are usually applied [21][22][23][24][25][26]. As mentioned above, this model has been solved for P-P, C-P and C-C conditions.…”
Section: The Effects Of the Boundary Conditionsmentioning
confidence: 99%
“…Since molecular dynamic simulations are difficult for large-scale systems, continuum mechanics models have been utilized to investigate the vibrational behavior of CNTs conveying fluid [64][65][66][67][68][69][70]. Natsuki et al [64] studied the wave propagation in single-or double-walled carbon nanotubes (DWCNTs) filled with internal flowing fluids by using an elastic shell model.…”
Section: Vibrations Of Nanotubes Conveying Fluidmentioning
confidence: 99%
“…In 2007, Reddy et al [67] investigated the effect of fluid flow on the free vibration and instability of fluid-conveying single-walled carbon nanotubes (SWCNTs), using both atomistic and Euler beam models. Wang et al [68] reported some results of an investigation into the influence of internal flowing fluid on the coupling vibration of fluid-filled CNTs; again, the Euler beam model was used. Recently, Wang and Ni [69] further analyzed the fluid-conveying CNT model developed by Yoon et al [65] and explored the possible postdivergence flutter existing in the same dynamical model.…”
Section: Vibrations Of Nanotubes Conveying Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuum simulations of the vibration (Lee and Chang, 2009;Wang et al, 2007;Yoon et al, 2005Yoon et al, , 2006Reddy et al, 2007) or wave propagation (Dong et al, 2008;Natsuki et al, 2007) of CNTs conveying fluid, the CNTs were modeled as a shell or beam, with the inner fluid regarded as a continuum fluid. However, although previous experiments (Rao et al, 2001;Garg ct al., 1998;Treacy et al, 1996;Poncharal et al, 1999) have shown that the application of a shell (He et al, 2005;Hu et al, 2008) or beam model (Sudak, 2003) to CNTs is largely reasonable, whether the inner fluid should be regarded as a continuum, the basic assumption of continuum fluid mechanics (Paidoussis, 1998), is more questionable.…”
Section: Introductionmentioning
confidence: 99%